Identifying root causes and mitigation measures of construction fall accidents / Normadiana Mohammad Hanapi...[et. al.] - Mohammad Hanapi, Normadiana; Mohd Kamal, Mohd Mawardi; Ismail, Muhammad Isha; Putera Abdullah, Indra Akmal (Universiti Teknologi MARA Cawangan Pahang, 2013)
The construction industry is one of the most hazardous industries. It is because those who spend their working lives on construction sites have a higher probability of being killed at their workplace. Based on the statistics issued by the Social Security Organization (SOCSO) Malaysia, the number of fatality and permanent disabilities due to fall from height accidents at the construction sites is one of the highest rates as compared to other sectors. Therefore, this research intends to identify the causes and safety measures of construction fall accidents in Shah Alam construction sites because there are a lot of high rise building projects in this state. This study is carried out by doing literature review and getting feedback through questionnaires. In order to find out causes and mitigation measures of fall accidents at the construction site, this study used SPSS test such as Spearman’s Rho to analyze the data. The finding of this study indicates that “poor safety attitude and behavior of workers” are the main problems in obstructing the implementation of safety procedures and guidelines for construction sites. The responses from the survey also show that “sufficient safety training” and “equipment for working at height” are the adoptable mitigation measures to enhance the workers’ safety performance. It is believed that appointing safety officers in inspection and maintenance works and by applying risk assessment in identifying fall hazards could reduce the number of fall accidents.